Pembangunan Sistem E-Learning Berbasis Web Sebagai Sarana Penunjang Pembelajaran Pada Madrasah Ibtidaiyah Negeri 2 Kota Malang - Rini Agustina; Hari Lugis Purwanto; Darul Huda (SMATIKA JURNAL : STIKI Informatika Jurnal, 2020)
This research focuses on discussing the results of research on The Development of E-learning System-based Web as a tool of Supporting Learning in Madrasah Ibtidaiyah Negeri 2 Kota Malang. The emergency condition experienced by people all over the world, even in Indonesia, namely the COVID-19 pandemic makes the pattern of teaching in the world of education switch to online-based. Schools should consider distance-learning strategies following the competencies that each school has, whether from the competencies of teachers, students, parents, or facilities. Therefore, teachers need basic teaching skills from face-to-face to virtual online or online. This research was conducted in the school year 2019-2020, the test subjects are teachers and students in Madrasah Ibtidaiyah Negeri 2 Kota Malang. This E-learning system has three access rights, namely administrators, teachers, and students who have different functions. Administrators have access rights to manage data on the system, teachers have the right to upload materials and practice questions on the system, while students can download materials and practice questions and be able to know their grades directly on the system. Measurement of application eligibility level is carried out using the user acceptance test (UAT) that has been filled and obtained the average result of 86% of the 30 respondents who agreed if this web-based E-learning application was used in Madrasah Ibtidaiyah Negeri 2 Kota Malang.